KORELASI ANTARA KADAR TUMOR NECROSIS FACTOR - Î± DAN PROFIL TROMBOSIT PADA PENDERITA SIROSIS HATI - , NUR RACHMANI INDRAWATI; , Dr. Neneng Ratnasari., SpPD-KGEH. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background. Tumor necrosis factor-Î± is a major cytokine involved in various forms of liver injury. TNF-Î± levels increased in liver cirrhosis and allegedly associated with liver cirrhosis related complications. Tumor necrosis factor can cause thrombocytopenia by reducing platelet lifespan. Platelet impairment in cirrhosis may be due to low production of platelets, increased splenic sequestration / platelet consumption, decreased platelet survival and low thrombopoetin level in liver cirrhosis. Low mean platelet volume (MPV) can be found in liver cirrhosis with thrombocytopenia. Platelet distribution width (PDW) values increased in liver cirrhosis. The degree of severity of thrombocytopenia increased with the addition of fibrosis. Purpose. This study is aimed to determine whether there was correlation between the levels of TNF-Î± and platelet profile in liver cirrhosis patients. Method. This study was cross-sectional study design. Research began in November 2010 until November 2011 (total sample met). Subjects were patients with liver cirrhosis who visited to the Gastroentero-hepatology clinic or treated in the department of Internal Medicine ward Dr Sarjito Hospital, who meet the inclusion and exclusion criteria. Venous blood tests done to measure the levels of TNF-Î± and platelet profiles including platelet numbers (AT), mean platelet volume (MPV), and platelet distribution width (PDW). We analized correlation between the levels of TNF-Î± and platelet profiles using Spearman nonparametric analysis for data not normally distributed. Level of significance was P <0.05. Results. There were 36 research subjects. The mean levels of TNF-Î± were 28.3 pg / ml (19.4 to 90.4), mean of platelet numbers were 93 thousand / mmk (40-307), mean of MPV values were 10.5 fL (6.80 to 13.50), mean of PDW values were 16,01 Â± 2.21%. There was no statistically significant correlation between the levels of TNF-Î± with the number of platelets (r = -0.180, p = 0.295), the value of MPV (r = -0.253, p = 0.137) and the value of PDW (r = 0.05